2014
DOI: 10.1039/c3cs60298b
|View full text |Cite
|
Sign up to set email alerts
|

Chiral metal nanoparticle-catalyzed asymmetric C–C bond formation reactions

Abstract: Chiral ligand-modified metal nanoparticles possess an attractive potential for application in asymmetric synthesis. This article focuses on chiral-nanoparticle-catalyzed asymmetric C-C bond formation reactions and discusses the nature of the active species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(88 citation statements)
references
References 156 publications
(161 reference statements)
0
88
0
Order By: Relevance
“…Heterogeneous asymmetric catalysts with bimetallic NPs have also been successfully developed in recent years. 91 Kobayashi and coworkers demonstrated that polymer-incarcerated chiral Rh/Ag NPs are effective for the asymmetric 1,4-addition reactions of arylboronic acids to α,β-unsaturated carbonyl compounds. [103][104] The composition of the bimetallic Rh/Ag NP and the type of chiral ligand affected catalytic activity and the amount of metal leaching.…”
Section: Chiral Ligands and Modifiers For Asymmetric Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous asymmetric catalysts with bimetallic NPs have also been successfully developed in recent years. 91 Kobayashi and coworkers demonstrated that polymer-incarcerated chiral Rh/Ag NPs are effective for the asymmetric 1,4-addition reactions of arylboronic acids to α,β-unsaturated carbonyl compounds. [103][104] The composition of the bimetallic Rh/Ag NP and the type of chiral ligand affected catalytic activity and the amount of metal leaching.…”
Section: Chiral Ligands and Modifiers For Asymmetric Catalysismentioning
confidence: 99%
“…[87][88][89][90][91][92] Such catalysts can be more useful than the traditional homogeneous asymmetric catalysts due to the advantages of easy separation, efficient recycling, and overall lower costs. For example, palladium NPs modified by chiral ligands has drawn much attention in the field of asymmetric catalysis [93][94][95][96] (the in-depth discussion of these systems is outside the scope of this Perspective, as the discrimination between homogeneous and heterogeneous catalysis is often challenging for Pd catalysts).…”
Section: Chiral Ligands and Modifiers For Asymmetric Catalysismentioning
confidence: 99%
“…Functionalization of metal NPs using chiral ligands have been used for enantioselective catalysis. [31] These developments are opening new aspects in tailoring colloidal NPs for catalytic processes whereby ligands are not merely spectator species but play a role in mediating the reaction through specific interactions with reacting species, similar to ligand acceleration effects in homogeneous systems. From a NP design perspective, manipulating surface chemistry through functionalization can be achieved by ligand exchange in many colloidal systems.…”
Section: Molecular Engineering Of the Nanoparticle Surfacesmentioning
confidence: 99%
“…Even if more and more organic transformations are using metal nanoparticles (MNPs) as catalysts [1][2][3][4][5][6], few of them concern enantioselective processes (for selected reviews, see [7][8][9][10]). The enantioselective catalysis on surfaces is commonly explained by three main mechanisms: the presence of chiral crystalline atomic structures at the surface, chiral adsorbates which modify the surface and chiral modifiers which control the approach of the substrate on the surface [11,12].…”
Section: Introductionmentioning
confidence: 99%